Comparative genoprotection ability of wild-harvested vs. aqua-cultured Ulva rigida coupled with phytochemical profiling. Issue 1 (2nd January 2021) - Marques, Ana; Ferreira, João; Abreu, Helena; Pereira, Rui; Pinto, Diana; Silva, Artur; Gaivão, Isabel; Pacheco, Mário
Abstract: Antigenotoxic properties of plant- and plant-like derived foods may embody nutritional strategies against DNA damage. Marine macroalgae have shown DNA-protective effects, but their nutraceutical potential and the influence of growing conditions on these properties is underexplored. Hence, we aimed to assess the genoprotection potential of wild-harvested vs . aquacultured Ulva rigida on Drosophila melanogaster, following a dietary exposure, in the presence and absence of a genotoxic agent (streptonigrin) using phytochemical profiling. DNA damage was evaluated with a single cell gel electrophoresis (comet) assay improved with endonucleases. An origin-based phytochemical profile was found, with aquacultured algae showing higher relative amounts of fatty alcohols, sterols, sesquiterpenoids and glycerol esters. Although U. rigida from both sources showed a DNA-protective action, especially against streptonigrin-induced genotoxicity, aquacultured algae demonstrated higher potential, which may be linked to the distinctive phytochemical profile. Overall, this study provided scientific evidence for the genoprotective activity of U. rigida and its confirmation as a functional food.